Video games, crime and next-gen deviance : reorienting the debate - Kelly, Craig; Lynes, Adam; Hoffin, Kevin (Emerald points., 2020)
The ebook edition of this title is Open Access, thanks to Knowledge Unlatched funding, freely available to read online. Drawing on the emerging deviant literature perspective, this book explores a range of culturally embedded harms and other activities to offer new insight on the idea that video games are intertwined with forms of deviancy.